Implementering av en torrhamn i Sverige - Vad är utmaningen? - Barry, Fredrik; Söderberg, Sofie (My University, 2016)
90% of all transported goods has at some point been transported by sea. The current trend for shipping lines are to build larger vessels which demands a higher efficiency at the port terminals. The port terminal in their turn then requires good flow of containers for inland transportation. One way to cope with the increasing flow of goods is to establish dry ports within the country and connect them to a port by rail. Although it is a very popular and effective method abroad it has proved difficult to establish the dry port concept in Sweden. This report will examine what the struggles are with the concept. In order to achieve a result semi-structured interviews have been conducted with persons in the shipping and transport industry in order to get an overall picture of the ability of dry ports in Sweden. There are different views of the need and effectiveness of a dry port as the railroad struggles with reliability and freight rates higher compared to other means of transport. Sweden is a country with long coastlines which affects the establishment of dry ports. Forwarders often use a combination of feeder vessel’s and trucks as it is a more efficient and cost-conscious alternative. In order for the dry port concept to succeed in Sweden there is a need for a more efficient and reliable railway system.
Keywords: Transport; Transportteknik och logistik; Transport; Transport Systems and Logistics